RECOMMENDED STUDY OF EXTINGUISHING METHODS BASED ON THE 1994 PETTIFER AND FOOKES CRITERIA APPROACH TO THE PLANNING OF THE TRANS-PAPUA WASIOR-NABIRE ROAD: STUDI REKOMENDASI METODE PENGGALIAN BERDASARKAN PENDEKATAN KRITERIA PETTIFER DAN FOOKES 1994 PADA PERENCANAAN RUAS JALAN TRANS PAPUA WASIOR-NABIRE - Arif Setiawan; Sampary William Wakum; Ismiyati; Louis Hermanus Lamma (INTAN Jurnal Penelitian Tambang, 2023)
The road is one of the traffic infrastructures for driving which supports all community activities. One of the stages of road construction is land clearing, in which one of the activities is eviction or excavation. The road construction location is the Trans Papua Wasior-Nabire road, Yamor District, Kaimana Regency, West Papua Province. However, the problem in this study is whether the excavation method is suitable for excavating material for road construction. Based on these problems, the purpose of this study is to recommend a method of excavation on the Trans Papua Wasior-Nabire road section. The method used is the Pettifer and Fookes (1994) criterion approach to determine the capability method. The results obtained with this approach indicate that the KM 501+500 excavation site is included in the level of easy digging capability or enters into a condition that is easy to dig. At the KM 502+100 excavation site, it is included in the hard digging capability level or a category that is difficult to dig because of the condition of the material which is difficult to dig, so the recommendation given is to use heavy equipment, namely a hydraulic excavator (backhoe) or a power shovel.